Minimally invasive sacroiliac fusion, a case series, and a literature review - Amer Mohammad H.; Elnahal Walid A.; Khaled Sherif A.; Abdel-Kader Khaled F.M.; Cass Michael A.; Gibbs James; Stott Philip M. (SICOT-J, 2022)
Introduction: Non-autoimmune sacroiliac joint pain contributes to nearly a quarter of low back pain patients. Non-surgical management fails to satisfy patients. A new minimally invasive technique for sacroiliac stabilization has been introduced, defying the traditional rules of fusion. The results outside explanatory trials and in day-to-day practice have not been reported. Materials and methods: This case series includes 20 patients diagnosed with chronic sacroiliac pain resistant to conservative management for at least 6 months. The diagnosis was confirmed with a positive sacroiliac injection. Patients underwent stabilization using the iFuse® implant. Patients were followed up for a minimum of one year. The primary outcome was the functional outcomes, assessed using VAS, ODI, and SF36. Secondary procedure rates, complication rates, and radiological assessments of fusion were collected as secondary outcomes. Results: At one year, the mean VAS score improved from 81.25 ± 10.7 SD preoperatively to 52.5 ± 26.8, p-value 0.0013. The mean ODI improved from 54.8 ± 11.21 SD preoperatively to 41.315 ± 15.34, P value = 0.0079. The mean PCS and MCS of SF36 improved by 17 and 20 points, respectively. Only 55% of patients achieved the MCID for the VAS score. 35% of the cohort had secondary procedures. Discussion: Minimally invasive sacroiliac fusion resulted in an improvement in mean functional scores with a wide dispersion. Patients not achieving MCID are patients with either a malpositioned implant, an associated lumbar pathology, or an inaccurate diagnosis. Our results are underwhelming compared to similar work but are still better than conservative cohorts in comparative studies. Conclusion: Minimally invasive sacroiliac fusion can be used successfully in select patients. Attention to diagnosis and surgical technique can improve the reproducibility of results.